A novel 2-d wavelength-time optical code division multiple access (OCDMA) code for high-performance system - Amir Razif Arief Jamil Abdullah (School of Computer and Communication Engineering, 2013)
The major contribution of the research work presented is the novel coding technique to enhance the system performance of the 2-D OCDMA network. The focus is on a development of newly 2-D wavelength-time spreading code sequences OCDMA system applied to the balance detection technique. The work establishes a mathematical model calculation for deriving bit error rate in OCDMA system based on the new 2-D modified double weight (MDW) OCDMA code.